Laminated film

By using a propylene-based polymer and inorganic oxide layer that meets specific conditions, the problem of the appearance of the stretchless polypropylene film with evaporated metal oxides is solved, and the appearance of the laminated film is improved, improving the rigidity and heat resistance, and excellent gas barrier properties are achieved.

CN119894675APending Publication Date: 2025-04-25PRIME POLYMER CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380067524.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-27
Filing Date
2023-09-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing stretchless polypropylene film with evaporated metal oxides has a problem of many wrinkles in appearance and needs to be improved.

Method used

The appearance of the film is improved by using a propylene-based polymer that meets specific conditions as the material of the non-stretch polypropylene film, combined with the design of the inorganic oxide layer. Specific conditions include the melt flow rate between 3-25 g/10 minutes, the ratio of weight average molecular weight to number average molecular weight is 6-15, and the ratio of Z-average molecular weight to number average molecular weight is 40-150.

Benefits of technology

The appearance of the laminated film is improved, the occurrence of wrinkles is reduced, the rigidity and heat resistance of the film are improved, and the gas barrier is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005320626430000171
    Figure BDA0005320626430000171
  • Figure BDA0005320626430000191
    Figure BDA0005320626430000191
  • Figure BDA0005320626430000201
    Figure BDA0005320626430000201
Patent Text Reader

Abstract

The present invention provides a laminated film having improved appearance (i.e., less wrinkles), that is, a laminated film having improved degree of occurrence of wrinkles and less wrinkles. The laminated film has an unstretched polypropylene film and an inorganic oxide layer in contact with the unstretched polypropylene film. The unstretched polypropylene film contains a propylene polymer that satisfies the following conditions (i) to iii: (i) the melt flow rate (MFR) measured under the conditions of 230 DEG C and a load of 2.16 kgf is in the range of 3-25 g / 10 minutes; (ii) the ratio (Mw / Mn) of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) measured by GPC is in the range of 6-15; (iii) The ratio (Mz / Mn) of the Z-average molecular weight (Mz) to the number-average molecular weight (Mn) measured by GPC is in the range of 40-150.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated film, and more particularly to a laminated film having a polypropylene film and an inorganic oxide layer. Background Art

[0002] Propylene polymers are widely used as materials for various molded bodies (e.g., Patent Documents 1 or 2). For example, films made of propylene polymers are widely used as packaging films for food or general merchandise due to their excellent mechanical properties such as rigidity and optical properties such as gloss. In addition, it is known that unstretched polypropylene films are excellent in rigidity and heat resistance in a well-balanced manner.

[0003] In order to preserve food for a long time, packaging materials with excellent gas barrier properties are needed to block oxygen or water vapor from external gases that promote corruption or deterioration. In the past, aluminum foil, aluminum vapor-deposited film, polyvinylidene chloride coating film, ethylene-vinyl alcohol film, etc. were used as raw materials with gas barrier properties. However, in recent years, as restrictions on environmental issues have been expanded, the use of raw materials such as aluminum foil that produce incineration residues has been restricted. In addition, there are problems such as the content of aluminum foil or aluminum vapor-deposited film cannot be seen and cannot be heated in a microwave oven.

[0004] On the other hand, transparent gas barrier films are known that are formed by vapor-depositing oxides such as silicon oxide or aluminum oxide on an unstretched polypropylene film (e.g., Patent Documents 3 or 4). Such films have advantages such as excellent gas barrier properties, low environmental load, ability to confirm contents, and suitability for use in microwave ovens.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-302858

[0008] Patent Document 2: Japanese Patent Application Publication No. 2006-045446

[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 9-156021

[0010] Patent Document 4: Japanese Patent Application Laid-Open No. 9-143294 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] However, currently, from the viewpoint of appearance (ie, many wrinkles), there is still room for further improvement in the unstretched polypropylene film on which metal oxides are deposited.

[0013] Therefore, an object of the present invention is to provide a laminated film having an improved appearance (ie, less wrinkles).

[0014] Technical solutions for solving technical problems

[0015] The inventors of the present invention have conducted intensive studies and have found that the appearance can be improved by using a propylene polymer satisfying the conditions (i) to (iii) as the propylene polymer of the unstretched polypropylene film, thereby completing the present invention.

[0016] The present invention relates to, for example, the following [1] to [5].

[0017] [1] A laminated film comprising an unstretched polypropylene film and an inorganic oxide layer in contact with the unstretched polypropylene film, wherein the unstretched polypropylene film contains a propylene polymer satisfying the following conditions (i) to (iii):

[0018] (i) a melt flow rate (MFR) in the range of 3 to 25 g / 10 min measured at 230° C. and 2.16 kgf load;

[0019] (ii) a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) measured by GPC is in the range of 6 to 15;

[0020] (iii) The ratio (Mz / Mn) of the Z average molecular weight (Mz) to the number average molecular weight (Mn) measured by GPC is in the range of 40 to 150.

[0021] [2] The laminated film according to [1], which has gas barrier properties.

[0022] [3] The laminated film according to [1] or [2], wherein the tensile elastic modulus at 80°C is 800 MPa or more.

[0023] [4] The multilayer film according to any one of [1] to [3], wherein the inorganic oxide layer has a thickness of 20 to 150 nm.

[0024] [5] The laminated film according to any one of [1] to [4], further comprising a biaxially stretched polypropylene film on the side opposite to the unstretched polypropylene film via an adhesive layer in contact with the inorganic oxide layer.

[0025] Effects of the Invention

[0026] The present invention can provide a laminated film with improved appearance (ie, less wrinkles). In other words, it is possible to provide a laminated film with improved wrinkle occurrence and less wrinkles. DETAILED DESCRIPTION

[0027] Hereinafter, the present invention will be described in more detail.

[0028] [Laminated film]

[0029] The laminated film of the present invention comprises a non-oriented polypropylene film (hereinafter referred to as "CPP film") and an inorganic oxide layer in contact with the CPP film.

[0030] 〔CPP film〕

[0031] (Propylene polymer)

[0032] The CPP film contains a propylene polymer satisfying the following conditions (i) to (iii).

[0033] Condition (i):

[0034] The melt flow rate (MFR) measured at 230° C. and a load of 2.16 kgf is 3 to 25 g / 10 minutes, preferably 4 to 23 g / 10 minutes, and more preferably 4 to 22 g / 10 minutes.

[0035] On the other hand, if the MFR is too small compared to the lower limit, the smoothness and gas barrier properties of the produced film decrease, while if the MFR is too large compared to the upper limit, the discharge amount from the extruder during film production decreases, thereby reducing productivity.

[0036] Condition (ii):

[0037] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by GPC (gel permeation chromatography) under the conditions used in the examples described below is in the range of 6 to 15, preferably 7 to 15, and more preferably 7 to 14.

[0038] On the other hand, when the Mw / Mn is too small compared to the lower limit, the elastic modulus of the produced film is insufficient, and when the Mw / Mn is too large compared to the upper limit, the smoothness of the produced film decreases.

[0039] Condition (iii):

[0040] The ratio (Mz / Mn) of the Z average molecular weight (Mz) to the number average molecular weight (Mn) measured by GPC is in the range of 40-150, preferably 40-140, and more preferably 40-135.

[0041] On the other hand, when the Mz / Mn is too small compared to the lower limit, the elastic modulus of the produced film is insufficient, and when the Mz / Mn is too large compared to the upper limit, the smoothness of the produced film decreases.

[0042] In the present invention, by using a propylene polymer that satisfies the above conditions (ii) and (iii), i.e., a wide molecular weight distribution, the degree of orientation of the propylene polymer molecules in the MD direction of the film is increased during film forming, thereby making the film highly rigid. In addition, by orientation, the crystallization of the propylene polymer is promoted, and the heat resistance of the film is also improved. As a result, it is speculated that the rigidity of the film can be maintained during the vapor deposition process at a high processing temperature, so that a laminated film with excellent appearance, i.e., a CPP film with an inorganic oxide layer, can be obtained.

[0043] Examples of the propylene polymer include propylene homopolymers, propylene copolymers, and mixtures thereof. Examples of the mixture include mixtures of multiple propylene homopolymers, mixtures of multiple propylene copolymers, and mixtures of more than one propylene homopolymer and more than one propylene copolymer. In the case of a mixture, as long as the mixture as a whole satisfies the above conditions (i) to (iii), each of the components contained in the mixture does not necessarily have to satisfy the above conditions (i) to (iii).

[0044] A preferred embodiment of the propylene-based polymer is a propylene homopolymer. The laminated film of the present invention obtained from the propylene homopolymer satisfying the above conditions (i) to (iii) has an excellent appearance, that is, has few wrinkles.

[0045] Another preferred embodiment of the propylene-based polymer is a copolymer of propylene and an α-olefin having 2 to 8 carbon atoms (excluding propylene).

[0046] Examples of the α-olefins include ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. The α-olefins may be used alone or in combination of two or more.

[0047] In the above-mentioned copolymer of propylene and α-olefins having 2 to 8 carbon atoms (excluding propylene), the content ratio of structural units derived from propylene is preferably 90% by mass or more, more preferably 92% by mass or more, further preferably 96% by mass or more, further more preferably greater than 98% by mass, and particularly preferably 98.6% by mass or more, and the content ratio of structural units derived from α-olefins having 2 to 8 carbon atoms (excluding propylene) is preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 4% by mass or less, further more preferably less than 2% by mass, and particularly preferably 1.4% by mass or less. The above-mentioned content ratio can be used 13 The measurement was performed by C-NMR.

[0048] The laminated film of the present invention obtained from the copolymer of propylene and an α-olefin having 2 to 8 carbon atoms (excluding propylene) having a content ratio of structural units derived from the α-olefin having 2 to 8 carbon atoms (excluding propylene) within the above range has excellent appearance, i.e., few wrinkles.

[0049] The propylene homopolymer and the copolymer of propylene and an α-olefin having 2 to 8 carbon atoms (excluding propylene) may each contain at least one biomass-derived monomer (propylene, an α-olefin having 2 to 8 carbon atoms (excluding propylene)). The monomers of the same type constituting the polymer may be only biomass-derived monomers, only fossil fuel-derived monomers, or both. Biomass-derived monomers include fungi, yeast, algae, and bacteria, and are monomers obtained from all renewable natural raw materials and their residues such as plant or animal sources. As carbon, 1×10 -12 The ratio of about 14 C isotope, the biomass carbon concentration (pMC) measured according to ASTM D6866 is about 100 (pMC). Biomass-derived monomers (propylene, α-olefins having 2 to 8 carbon atoms (excluding propylene)) can be obtained, for example, by conventional methods. From the viewpoint of reducing environmental load, it is preferred that the homopolymer and / or the copolymer contain biomass-derived monomers. As long as the polymer production conditions such as the polymerization catalyst and the polymerization temperature are the same, even if the raw material olefin is a propylene-based polymer containing a biomass-derived olefin, the ratio of 1×10 -12 The ratio of about 14 The molecular structure other than the C isotope is the same as that of propylene-based polymers made from fossil fuel-derived monomers, so the performance does not change.

[0050] The above-mentioned propylene homopolymer and copolymer of propylene and α-olefin having 2 to 8 carbon atoms (excluding propylene) may each contain at least one or more monomers of chemical recovery origin (propylene, α-olefin having 2 to 8 carbon atoms (excluding propylene)). The same type of monomers constituting the polymer may be only monomers of chemical recovery origin, or may include monomers of chemical recovery origin and monomers of fossil fuel origin and / or monomers of biomass origin. The monomers of chemical recovery origin (propylene, α-olefin having 2 to 8 carbon atoms (excluding propylene)) can be obtained, for example, by a currently known method. From the viewpoint of reducing environmental load (mainly reducing waste), it is preferred that the above-mentioned homopolymer and / or the above-mentioned copolymer contain monomers of chemical recovery origin. Monomers of chemical recovery origin are monomers obtained by degrading polymers such as waste plastics into monomer units such as propylene by depolymerization, thermal decomposition, etc., and monomers produced using the monomers as raw materials. Therefore, even if the raw material monomer is a propylene-based polymer containing monomers of chemical recovery origin, as long as the polymer production conditions such as the polymerization catalyst, polymerization process, and polymerization temperature are the same, the molecular structure is the same as that of a propylene-based polymer composed of monomers of fossil fuel origin. Therefore, the performance will not change.

[0051] Preferred examples of the propylene-based polymer include a propylene-based polymer composition (X) comprising a propylene homopolymer (A) and a propylene-based polymer (B) as described below.

[0052] <Propylene homopolymer (A)>

[0053] The melt flow rate (MFR) of the propylene homopolymer (A) measured at 230°C and a load of 2.16 kgf is preferably in the range of 5 to 40 g / 10 min, more preferably 7 to 35 g / 10 min.

[0054] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the propylene homopolymer (A) is preferably in the range of 3.0 to 8.0, more preferably 3.5 to 6.0.

[0055] When the Mw / Mn of the propylene homopolymer (A) is within the above range, the laminated film of the present invention has excellent rigidity and transparency.

[0056] 《Method for producing propylene homopolymer (A)》

[0057] The propylene homopolymer (A) can be produced by homopolymerizing propylene using a catalyst, and may be a commercially available product.

[0058] As catalysts, for example, there can be listed: catalysts formed from solid catalyst components containing magnesium, titanium and halogen as essential components, organic metal compound catalyst components such as organic aluminum compounds, and electron donating compound catalyst components such as organic silicon compounds (as representative catalysts, the catalysts described in paragraphs

[0050] to

[0075] of International Publication No. 2021 / 025142); metallocene catalysts using metallocene compounds as one component of the catalyst.

[0059] <Propylene polymer (B)>

[0060] The propylene polymer (B) contains 20 to 50% by mass of a propylene polymer (b1) having an intrinsic viscosity [η] of 8 to 12 dL / g as measured at 135°C in a tetralin solvent, and 50 to 80% by mass of a propylene polymer (b2) having an intrinsic viscosity [η] of 0.5 to 1.5 dL / g as measured at 135°C in a tetralin solvent [wherein the total amount of (b1) and (b2) is 100% by mass].

[0061] Hereinafter, the intrinsic viscosity [η] measured at 135° C. in a tetralin solvent may also be simply referred to as “intrinsic viscosity [η]”.

[0062] 《Propylene polymer (b1)》

[0063] The intrinsic viscosity [η] of the propylene polymer (b1) is in the range of 8 to 12 dL / g, preferably in the range of 10 to 12 dL / g, and more preferably in the range of 10.5 to 11.5 dL / g.

[0064] When the intrinsic viscosity [η] is above the above lower limit, the laminated film of the present invention has excellent rigidity and heat resistance. When the intrinsic viscosity [η] is below the above upper limit, a CPP film can be produced with excellent formability, and the laminated film of the present invention has excellent surface appearance.

[0065] The mass fraction of the propylene polymer (b1) in the propylene polymer (B) is in the range of 20 to 50 mass %, preferably 20 to 45 mass %, more preferably 20 to 40 mass %, further preferably 22 to 40 mass %.

[0066] When the mass fraction is above the lower limit, the propylene polymer composition (X) has sufficient melt tension and can produce a CPP film having excellent rigidity and heat resistance. When the mass fraction is below the upper limit, the occurrence of poor appearance can be suppressed when the propylene polymer composition (X) is formed.

[0067] Examples of the propylene polymer (b1) include homopolymers of propylene and copolymers of propylene and α-olefins having 2 to 8 carbon atoms (excluding propylene). Examples of α-olefins having 2 to 8 carbon atoms include ethylene, 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene. Ethylene is preferred among these α-olefins. One or more α-olefins may be used.

[0068] In the copolymer of propylene and α-olefin having 2 to 8 carbon atoms, the content of the structural unit derived from propylene is usually 90% by mass or more, preferably 95% by mass or more, more preferably 98% by mass or more, and the content of the structural unit derived from α-olefin having 2 to 8 carbon atoms (excluding propylene) is usually 10% by mass or less, preferably 5% by mass or less, more preferably 2% by mass or less. The above content can be obtained by 13 The measurement was performed by C-NMR.

[0069] The propylene-based polymer (b1) may be used alone or in combination of two or more.

[0070] <<Propylene polymer (b2)>>

[0071] The intrinsic viscosity [η] of the propylene polymer (b2) is in the range of 0.5 to 1.5 dL / g, preferably 0.6 to 1.5 dL / g, more preferably 0.8 to 1.5 dL / g.

[0072] When the intrinsic viscosity [η] is at least the above lower limit, sufficient melt tension can be imparted to the propylene polymer (B), and when the intrinsic viscosity [η] is at most the above upper limit, a CPP film can be produced with excellent moldability.

[0073] The mass fraction of the propylene polymer (b2) in the propylene polymer (B) is in the range of 50 to 80 mass %, preferably 55 to 80 mass %, more preferably 60 to 80 mass %, further preferably 60 to 78 mass %.

[0074] When the mass fraction is above the above lower limit, the occurrence of poor appearance can be suppressed when the above propylene polymer composition (X) is formed. When the mass fraction is below the above upper limit, sufficient melt tension can be imparted to the above propylene polymer (B), so that the rigidity and heat resistance of the laminated film of the present invention are excellent.

[0075] Examples of the propylene polymer (b2) include homopolymers of propylene and copolymers of propylene and α-olefins having 2 to 8 carbon atoms (excluding propylene). Examples of α-olefins having 2 to 8 carbon atoms include ethylene, 1-butene, 1-hexene, 1-octene, and 4-methyl-1-pentene. Ethylene is preferred among these α-olefins. One or more α-olefins may be used.

[0076] In the copolymer of propylene and α-olefin having 2 to 8 carbon atoms, the content of the structural unit derived from propylene is usually 90% by mass or more, preferably 93% by mass or more, and more preferably 94% by mass or more, and the content of the structural unit derived from α-olefin having 2 to 8 carbon atoms (excluding propylene) is usually 10% by mass or less, preferably 7% by mass or less, and more preferably 6% by mass or less. The above content can be obtained by 13 The measurement was performed by C-NMR.

[0077] The propylene-based polymer (b2) may be used alone or in combination of two or more.

[0078] "additive"

[0079] The propylene polymer (B) may be mixed with additives such as antioxidants, neutralizers, flame retardants, crystal nucleating agents, etc. as needed. One or more additives may be used. The proportion of the additives is not particularly limited and can be adjusted appropriately.

[0080] 《Physical properties of propylene polymer (B)》

[0081] The melt flow rate (MFR) of the propylene polymer (B) measured at 230°C and 2.16 kgf load is preferably in the range of 0.01 to 5 g / 10 min, more preferably 0.05 to 4 g / 10 min, and further preferably 0.1 to 3 g / 10 min. When the MFR of the propylene polymer (B) is in the above range, the film formability of the propylene polymer composition (X) is excellent.

[0082] Regarding the above-mentioned propylene-based polymer (B), in the total area of ​​the region surrounded by the molecular weight distribution curve measured by gel permeation chromatography (GPC), the area ratio occupied by the high molecular weight region with a molecular weight of 1.5 million or more (equivalent to the mass ratio of the high molecular weight component with a molecular weight of 1.5 million or more) is preferably 7% or more, more preferably 10% or more, and further preferably 12% or more. The upper limit of the above-mentioned area ratio is, for example, 30%, preferably 25%.

[0083] The area ratio of the high molecular weight region is more than a specific ratio, which means that the propylene polymer (B) contains a high molecular weight component with a molecular weight of 1.5 million or more. At least a part of the high molecular weight component is a high molecular weight component with an intrinsic viscosity [η] of 10 to 12 dL / g. Therefore, when the ratio of the high molecular weight component is within the above range, the melt tension of the propylene polymer (B) is more excellent.

[0084] The propylene polymer (B) preferably has two peaks in the molecular weight distribution curve measured by GPC. Among them, the ratio (MH / ML) of the peak molecular weight (MH) on the high molecular weight side to the peak molecular weight (ML) on the low molecular weight side is preferably 50 or more, more preferably 70 or more, and further preferably 90 or more. The upper limit of the ratio (MH / ML) is, for example, 500, preferably 300. The molecular weight distribution curve has two peaks, and MH / ML is above a specific value, which indicates that the content of the high molecular weight component in the polymer is high and its intrinsic viscosity [η] is also high. Therefore, the propylene polymer (B) of this mode contributes to the improvement of melt tension and contributes to the improvement of the rigidity and heat resistance of the film formed by the above-mentioned propylene polymer composition (X).

[0085] From the viewpoint of viscosity and film formability of the propylene polymer composition (X), the peak molecular weight ML on the low molecular weight side of the molecular weight distribution curve of the propylene polymer (B) measured by GPC is preferably 100,000 or less, more preferably 80,000 or less, and further preferably 50,000 or less.

[0086] 《Method for producing propylene polymer (B)》

[0087] As a method for producing the propylene-based polymer (B), various known production methods can be mentioned, and for example, the method described in paragraphs

[0038] to

[0075] of International Publication No. 2021 / 025142 can be mentioned.

[0088] <Propylene polymer composition (X)>

[0089] The propylene polymer composition (X) contains the propylene homopolymer (A) and the propylene polymer (B) in such a ratio that the entire composition satisfies the above conditions (i) to (iii), for example, such that the propylene homopolymer (A) accounts for 60 to 99% by mass, preferably 70 to 99% by mass, more preferably 70 to 97% by mass, and even more preferably 70 to 95% by mass, and the propylene polymer (B) accounts for 1 to 40% by mass, preferably 1 to 30% by mass, more preferably 3 to 30% by mass, and even more preferably 5 to 30% by mass [wherein the total amount of (A) and (B) is 100% by mass].

[0090] When the proportion of the propylene-based polymer (B) is not less than the above lower limit, the obtained CPP film and the laminated film of the present invention are excellent in rigidity (tensile elastic modulus).

[0091] When the proportion of the propylene-based polymer (B) is at most the above upper limit, the obtained CPP film and the laminated film of the present invention are excellent in transparency and appearance.

[0092] Since the propylene polymer (b1) has a high molecular weight, by mixing the propylene homopolymer (A) and the propylene polymer (B), a propylene polymer composition (X) satisfying the above conditions (ii) and (iii), i.e. having a wide molecular weight distribution, can be prepared.

[0093] <<Method for producing propylene polymer composition (X)>>

[0094] The propylene polymer composition (X) can be produced by any known method, for example, a method in which the propylene homopolymer (A) and the propylene polymer (B) and any additives as required are mixed using a Henschel mixer, a V-blender, a ribbon blender, a tumble blender, etc.; or a method in which after the above mixing, the mixture is melt-kneaded using a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, a roll, etc., and then pelletized or pulverized.

[0095] (additive)

[0096] The CPP film may contain additives such as weather stabilizers, heat stabilizers, antistatic agents, slip agents, anti-blocking agents, anti-fogging agents, nucleating agents, decomposing agents, pigments, dyes, plasticizers, hydrochloric acid absorbers, antioxidants, crosslinking agents, crosslinking accelerators, reinforcing agents, fillers, softeners, processing aids, activators, moisture absorbents, adhesives, flame retardants, and mold release agents within the range that does not impair the purpose of the present invention. One or more additives may be used.

[0097] The CPP film may contain a nucleating agent in order to improve transparency and heat resistance. Examples of the nucleating agent include sorbitol compounds such as dibenzylidene sorbitol, organic phosphate compounds, rosin acid salt compounds, C4-C12 aliphatic dicarboxylic acids and their metal salts. Among these, organic phosphate compounds are preferred. One or more nucleating agents may be used.

[0098] The amount of the nucleating agent in the CPP film is preferably 0.05 to 0.5 parts by mass, more preferably 0.1 to 0.3 parts by mass, based on 100 parts by mass of the propylene-based polymer.

[0099] The CPP film may contain a resin component (such as polyethylene) other than the propylene polymer, and the amount thereof is preferably 2 parts by mass or less, more preferably 1 part by mass or less, and further preferably 0.5 parts by mass or less, based on 100 parts by mass of the propylene polymer.

[0100] (CPP film)

[0101] The CPP film can be produced by molding the propylene-based polymer on a film.

[0102] Examples of the molding method include extrusion molding methods such as a T-die method and an inflation method, compression molding methods, calendar molding methods, and casting methods.

[0103] The CPP film can be formed, for example, as follows.

[0104] The above-mentioned propylene polymer and any additives can be directly put into the hopper of a film forming machine, or the above-mentioned components can be pre-mixed using a screw ribbon blender, Banbury mixer, Henschel mixer, high-speed mixer, etc., or further melt-kneaded using a single-screw extruder or twin-screw extruder, roll or other kneading machine to obtain the propylene polymer, and then film forming is performed.

[0105] A specific example of manufacturing a CPP film using the T-die method is described below. The above-mentioned components are added to an extruder, and melt-kneaded usually at a temperature of 180 to 280° C., preferably 200 to 270° C., and then extruded into a film using the die lip of a T-die. The molten film is cooled and pulled up by a puller using a clamping roll or the like to obtain a CPP film.

[0106] Examples of methods for cooling the molten film include: a cooling method using an air knife method or an air chamber method using rollers and air cooling; an extrusion cooling method using a polishing roller method, an oscillating roller method, a belt casting method, etc.; and a contact cooling method using a refrigerant such as a water cooling method.

[0107] The obtained CPP film may be subjected to a common film treatment method for film molding, for example, a corona discharge treatment or a liquid agent coating treatment.

[0108] <Inorganic oxide layer>

[0109] The laminated film of the present invention has an inorganic oxide layer.

[0110] The inorganic oxide layer may be formed by vapor-depositing an inorganic oxide on the CPP film.

[0111] Examples of the vapor deposition method include conventionally known methods such as a chemical vapor deposition method (CVD method) and a physical vapor deposition method (PVD method).

[0112] Examples of the inorganic oxides include inorganic oxides such as aluminum, zinc, magnesium, and silicon.

[0113] The thickness of the inorganic oxide layer measured by the method used in the examples described below is, for example, 20 to 150 nm, preferably 30 to 60 nm. When the thickness is within the above range, the laminated film of the present invention has excellent appearance and gas barrier properties.

[0114] 〔Laminated film〕

[0115] The laminated film of the present invention comprises the CPP film and the inorganic oxide layer in contact with the CPP film.

[0116] The laminated film of the present invention preferably has excellent gas barrier properties such as water vapor barrier properties and oxygen barrier properties.

[0117] The water vapor permeability is preferably 5 or less, and more preferably 1 or less. The water vapor permeability can be adjusted by, for example, changing the thickness of the vapor-deposited film.

[0118] The oxygen permeability is preferably 1000 or less, and more preferably 100 or less. It can be adjusted by changing the thickness of the vapor-deposited film.

[0119] The tensile modulus of the laminated film of the present invention at 80°C measured by the method used in the examples described below is preferably 800 MPa or more, more preferably 850 MPa or more, and its upper limit may be, for example, 1300 MPa. The value of the tensile modulus can be adjusted, for example, by changing the film drawing speed during film formation.

[0120] The laminated film of the present invention may have an arbitrary layer in addition to the CPP film and the inorganic oxide layer. By having an arbitrary layer, various functions can be imparted to the laminated film of the present invention. The arbitrary layer may be a single layer or multiple layers.

[0121] As the location for setting any layer, you can list:

[0122] the side of the CPP film opposite to the inorganic oxide layer;

[0123] A position between the CPP film and the inorganic oxide layer where the CPP film and the inorganic oxide layer are not in contact;

[0124] The inorganic oxide layer is on the opposite side to the CPP film.

[0125] As the optional layer, there can be listed a biaxially stretched polypropylene film, a CPP film (which may be a CPP film containing a propylene-based polymer satisfying the above-mentioned conditions (i) to (iii) or a CPP film different therefrom), a barrier layer against gases such as water vapor and oxygen, a sound absorbing layer, a light shielding layer, an adhesive layer, a bonding layer, a coloring layer, a conductive layer, and a recycled resin-containing layer.

[0126] Specific examples of the raw material for forming the optional layer include olefin-based polymer compositions other than the above-mentioned propylene-based polymers, gas barrier resin compositions, adhesive resin compositions, and the like.

[0127] Examples of a method for forming an arbitrary layer include a coextrusion method and an extrusion coating method.

[0128] As an arbitrary layer, it is preferred to have a biaxially stretched polypropylene film. A preferred embodiment of the laminated film of the present invention is to have a biaxially stretched polypropylene film on the opposite side of the above-mentioned unstretched polypropylene film, through a bonding layer in contact with the above-mentioned inorganic oxide layer. As the adhesive layer, adhesive resins such as tackifier coating agents such as polyurethane-based and isocyanate-based adhesives and modified polyolefins such as unsaturated carboxylic acid grafted polyolefins can be cited. Compared with a laminated film having a biaxially stretched polyethylene terephthalate film, a biaxially stretched nylon film, etc. as a biaxially stretched film, the above-mentioned laminated film is preferred from the viewpoint of single material and reduced environmental load.

[0129] The laminated film of the present invention can be used as a packaging material for, for example, food, beverages, industrial components, general merchandise, toys, daily necessities, office supplies, medical supplies, and the like.

[0130] The laminated film of the present invention can be used as a packaging film in a wide range of packaging fields, such as various food packaging fields such as fresh foods such as fish and meat, snacks, dried noodles, soups, pickles and other water-containing foods; medical products in various forms such as tablets, powders, liquids, etc., medical-related product packaging used for medical peripheral materials; and various electrical equipment packaging fields such as cassettes and electrical components.

[0131] Example

[0132] Hereinafter, one embodiment of the present invention will be described using examples, but the present invention is not limited to these examples.

[0133] (Measurement and evaluation of propylene polymers)

[0134] [Weight average molecular weight (Mw), number average molecular weight (Mn), Z average molecular weight (Mz) and molecular weight distribution (Mw / Mn, Mz / Mn)]

[0135] The weight average molecular weight (Mw), number average molecular weight (Mn), Z average molecular weight (Mz) and molecular weight distribution (Mw / Mn, Mz / Mn) were measured using GPC under the following conditions. In addition, a standard curve was prepared using commercially available monodisperse standard polystyrene, and the weight average molecular weight (Mw), number average molecular weight (Mn) and Z average molecular weight (Mz) were calculated based on the following conversion method.

[0136] (Measurement conditions)

[0137] Apparatus: Gel permeation chromatography HLC-8321GPC / HT (manufactured by Tosoh Corporation)

[0138] Organic solvent: o-dichlorobenzene

[0139] Column: 2 TSKgel GMH6-HT, 2 TSKgel GMH6-HTL columns (both manufactured by Tosoh Corporation)

[0140] Flow rate: 1.0mL / min

[0141] Sample: 0.10 mg / mL o-dichlorobenzene solution

[0142] Temperature: 140℃

[0143] Molecular weight conversion: PS conversion / universal calibration method

[0144] In the calculation of the universal correction, the Mark-Houwink viscosity coefficients were used. The Mark-Houwink coefficients of PS were the values ​​described in the literature (J. Polym. Sci., Part A-2, 8, 1803 (1970)).

[0145] [Production of propylene homopolymer (A)]

[0146] [Production of propylene homopolymer (A-1)]

[0147] [Production Example 1]

[0148] (1) Preparation of transition metal catalyst component (c-1)

[0149] Prepare a vibration mill equipped with 4 crushing tanks with an internal volume of 4L, and load 9kg of steel balls with a diameter of 12mm in each crushing tank. Add 300g of magnesium chloride, 115mL of diisobutyl phthalate, and 60mL of titanium tetrachloride to each tank in a nitrogen atmosphere, and crush the magnesium chloride for 40 hours. Add 75g of the obtained mixture to a 5L flask, add 1.5L of toluene, stir at 114°C for 30 minutes, then let stand and remove the supernatant. The obtained solid component is washed with 1.5L of n-heptane at 20°C for 3 times. Then, disperse in 1.5L of n-heptane to obtain a slurry of transition metal catalyst component (c-1). The obtained transition metal catalyst component (c-1) contains 2% by weight of titanium and 18% by weight of diisobutyl phthalate.

[0150] (2) Production of prepolymerized catalyst (d-1)

[0151] 100 g of transition metal catalyst component (c-1), 15.4 mL of triethylaluminum and 100 L of heptane were added to an autoclave with a stirrer having a content of 200 L, the internal temperature was maintained at 5°C, 600 g of propylene was added, and the propylene was polymerized by stirring for 60 minutes. After the polymerization was completed, 4.1 mL of titanium tetrachloride was added to obtain a prepolymerized catalyst (d-1). The prepolymerized catalyst (d-1) contained 6 g of polypropylene per 1 g of the transition metal catalyst component.

[0152] (3) Production of propylene homopolymer (A-1)

[0153] Into a 500L container-type polymerization reactor equipped with a stirrer, propylene was continuously supplied at 130kg / hour, hydrogen was continuously supplied at 136NL / hour, a prepolymerization catalyst (d-1) was continuously supplied at 1.05g / hour, triethylaluminum was continuously supplied at 5.2mL / hour, cyclohexylmethyldimethoxysilane was continuously supplied at 0.4mL / hour, and hydrogen was supplied so that the hydrogen concentration in the gas phase reached 2.6mol%. The temperature of the container-type polymerization reactor equipped with a stirrer was 73°C, and the pressure was 3.2MPa / G. After the obtained slurry was deactivated, propylene was evaporated to obtain a powdery propylene homopolymer (a-1). The MFR of the obtained propylene homopolymer (a-1) was 1.7g / 10min. With respect to 100 parts by mass of the obtained propylene homopolymer (a-1), 0.07 parts by mass of an organic peroxide PERHEXA25B-40 (NOF Corporation) was added and stirred sufficiently. This was melt-kneaded using a KTX 30 mm twin-screw extruder at a cylinder temperature of 230° C. and an extrusion rate of 25 kg / hour. The obtained propylene homopolymer (A-1) had an MFR of 9 g / 10 min and an Mw / Mn of 3.7.

[0154] [Production of propylene homopolymer (A-2)]

[0155] [Production Example 2]

[0156] (1) Preparation of solid titanium catalyst component (c-2)

[0157] 95.2 g of anhydrous magnesium chloride, 442 mL of decane and 390.6 g of 2-ethylhexyl alcohol were heated at 130° C. for 2 hours to form a uniform solution, and then 21.3 g of phthalic anhydride was added to the solution, and the mixture was stirred and mixed at 130° C. for 1 hour to dissolve the phthalic anhydride. The uniform solution thus obtained was cooled to room temperature, and then 75 mL of the uniform solution was added dropwise to 200 mL of titanium tetrachloride maintained at -20° C. over 1 hour. After the addition was completed, the temperature of the mixed solution was raised to 110° C. over 4 hours, and after reaching 110° C., 5.22 g of diisobutyl phthalate (DIBP) was added, and the mixture was stirred at this temperature for 2 hours from then on. After the 2-hour stirring was completed, the solid portion was collected by hot filtration, and the solid portion was resuspended in 275 mL of titanium tetrachloride and then heated at 110° C. for 2 hours. After the reaction is completed, the solid part is collected by hot filtration and fully washed with decane and hexane at 110°C until no free titanium compound is detected in the solution. The solid titanium catalyst component prepared as described above is stored in the form of hexane slurry, and a part of it is dried to adjust the catalyst composition. The solid titanium catalyst component contains 2.3% by weight of titanium, 61% by weight of chlorine, 19% by weight of magnesium, and 12.5% ​​by weight of DIBP.

[0158] (2) Production of prepolymerized catalyst (d-2)

[0159] 100.0 g of solid titanium catalyst component (c-2), 19.2 mL of cyclohexylmethyldimethoxysilane, 65.6 mL of triethylaluminum, and 10 L of heptane were added to an autoclave with a stirrer having a content of 20 L. The internal temperature was maintained at 15 to 20 ° C. 600 g of propylene was added and stirred for 100 minutes to polymerize propylene. After the polymerization was completed, the solid component was allowed to settle, and the supernatant was removed and washed with heptane twice. The obtained prepolymerized catalyst was resuspended in refined heptane and adjusted with heptane so that the solid catalyst component concentration reached 1.0 g / L.

[0160] (3) Production of propylene homopolymer (A-2)

[0161] Into a tubular polymerizer with an internal volume of 58 L, propylene was continuously supplied at 43 kg / hour, hydrogen was continuously supplied at 56 NL / hour, a prepolymerization catalyst (d-2) was continuously supplied at 0.77 g / hour, triethylaluminum was continuously supplied at 2.3 mL / hour, and cyclohexylmethyldimethoxysilane was continuously supplied at 4.3 mL / hour, and polymerization was carried out in a liquid-filled state without the presence of a gas phase. The temperature of the tubular polymerizer was 70°C and the pressure was 3.4 MPa / G. The obtained slurry was sent to a container-type polymerizer with an internal volume of 70 L and equipped with a stirrer for further polymerization. Propylene was continuously supplied at 45 kg / hour to the polymerizer, and hydrogen was supplied so that the hydrogen concentration in the gas phase reached 2.9 mol%. The polymerization was carried out at a polymerization temperature of 70°C and a pressure of 3.1 MPa / G. After the obtained slurry was deactivated, propylene was evaporated to obtain a powdery propylene homopolymer (A-2). The obtained propylene homopolymer (A-2) had an MFR of 9 g / 10 min and an Mw / Mn of 5.0.

[0162] [Production of propylene homopolymer (A-3)]

[0163] [Production Example 3]

[0164] (1) Preparation of solid titanium catalyst component (c-3)

[0165] 95.2 g of anhydrous magnesium chloride, 442 mL of decane and 390.6 g of 2-ethylhexyl alcohol were heated at 130° C. for 2 hours to form a uniform solution. 21.3 g of anhydrous phthalic acid was added to the solution, and the mixture was stirred and mixed at 130° C. for 1 hour to dissolve phthalic anhydride. The uniform solution thus obtained was cooled to room temperature, and 75 mL of the uniform solution was added dropwise to 200 mL of titanium tetrachloride maintained at -20° C. over 1 hour. After the addition was completed, the temperature of the mixed solution was raised to 110° C. over 4 hours. After reaching 110° C., 5.22 g of diisobutyl phthalate (DIBP) was added, and the mixture was stirred at this temperature for 2 hours. After the 2-hour reaction was completed, the solid portion was collected by hot filtration, and the solid portion was resuspended in 275 mL of titanium tetrachloride and heated at 110° C. for 2 hours. After the reaction is completed, the solid part is collected by hot filtration and fully washed with decane and hexane at 110°C until no free titanium compound is detected in the solution. The solid titanium catalyst component prepared as described above is stored in the form of hexane slurry, a part of which is dried to adjust the catalyst composition. The solid titanium catalyst component contains 2.3% by weight of titanium, 61% by weight of chlorine, 19% by weight of magnesium, and 12.5% ​​by weight of DIBP.

[0166] (2) Production of prepolymerized catalyst (d-3)

[0167] 100.0 g of solid titanium catalyst component (c-3), 22.4 mL of dicyclopentyldimethoxysilane, 65.6 mL of triethylaluminum, and 10 L of heptane were added to an autoclave with a stirrer having a content of 20 L. The internal temperature was maintained at 15 to 20 ° C. 600 g of propylene was added and stirred for 100 minutes to polymerize propylene. After the polymerization was completed, the solid component was allowed to settle, and the supernatant was removed and washed with heptane twice. The obtained prepolymerized catalyst was resuspended in refined heptane and adjusted with heptane so that the solid catalyst component concentration reached 1.0 g / L.

[0168] (3) Production of propylene homopolymer (A-3)

[0169] Into a tubular polymerizer with an internal volume of 58 L, propylene was continuously supplied at 43 kg / hour, hydrogen was continuously supplied at 163 NL / hour, a prepolymerization catalyst (d-3) was continuously supplied at 0.55 g / hour, triethylaluminum was continuously supplied at 1.9 mL / hour, and dicyclopentyldimethoxysilane was continuously supplied at 3.8 mL / hour, and polymerization was carried out in a liquid-filled state without the presence of a gas phase. The temperature of the tubular polymerizer was 70°C and the pressure was 3.5 MPa / G. The obtained slurry was sent to a container-type polymerizer with an internal volume of 70 L and equipped with a stirrer for further polymerization. Propylene was continuously supplied at 45 kg / hour to the polymerizer, and hydrogen was supplied so that the hydrogen concentration in the gas phase reached 15.8 mol%. The polymerization was carried out at a polymerization temperature of 63°C and a pressure of 3.2 MPaG. After the obtained slurry was deactivated, propylene was evaporated to obtain a powdery propylene homopolymer (A-3). The obtained propylene homopolymer (A-3) had an MFR of 30 g / 10 min and an Mw / Mn of 5.2.

[0170] [Production of propylene homopolymer (A-4)]

[0171] [Production Example 4]

[0172] As the propylene homopolymer (A-4), a propylene homopolymer having MFR: 7.2 g / 10 min, intrinsic viscosity [η]: 1.8 dL / g, melting point: 165° C., and Mw / Mn: 4.8 (trade name: Prime Polypro F107BA, manufactured by Prime Polymer Co., Ltd.) was used.

[0173] [Production of propylene polymer (B)]

[0174] [Production Example 5]

[0175] Propylene polymer (B) was produced according to Production Example 1 of International Publication No. 2021 / 025142. In this Production Example 5, propylene polymer (A-1), propylene polymer (a1-1) and propylene polymer (a2-1) in Production Example 1 of International Publication No. 2021 / 025142 were replaced with propylene polymer (B), propylene polymer (b1) and propylene polymer (b2), respectively.

[0176] Table 1 shows the physical properties of the propylene polymer (B) and the like measured in the same manner as in Production Example 1 of International Publication No. 2021 / 025142.

[0177] [Table 1]

[0178] Table 1

[0179]

[0180] [Comparative Example 1]

[0181] (Manufacturing of laminated film)

[0182] As a propylene-based polymer, the propylene homopolymer obtained in Production Example 1 (100 parts by mass) was prepared.

[0183] A film forming machine with a temperature set to 286°C, a screw diameter of 75 mm, and a T-die with a width of 600 mm at the front end of the extruder was used. The propylene polymer was fed into the extruder and extruded into a film. The film was then cooled using a cooling roll set to a temperature of 30°C to obtain a CPP film with a thickness of 25 μm.

[0184] In order to prepare a test piece, a part of the obtained CPP film was cut out, and an inorganic oxide layer was formed on the surface of the remaining part according to the following method.

[0185] Specifically, the formed film was cut into a width of 130 mm and placed in a vacuum deposition device equipped with a film take-up machine and a winder. -2 After the film is in a vacuum state of 1000 Pa, it is wound around a metal roll cooled at -20°C. Aluminum oxide or silicon oxide is heated and evaporated to deposit inorganic oxide on the surface of the film in contact with the cooling metal roll.

[0186] In this manner, a laminated film is obtained.

[0187] In order to evaluate the number of wrinkles described later, a laminated film of A4 size (210 mm in the vertical (TD) direction×290 mm in the MD direction) was prepared.

[0188] (Measurement and evaluation of laminated films)

[0189] 〔Thickness of inorganic oxide layer〕

[0190] The thickness of the inorganic oxide layer is measured as follows.

[0191] The obtained laminated film was cut with a microtome to expose a cross section, and the cross section was observed with a scanning electron microscope (SEM) to measure the thickness of the inorganic oxide layer. SEM observation was performed using Regulus 8220 manufactured by Hitachi High-Technologies Corporation with a reflected electron detector.

[0192] 〔Tensile elastic modulus〕

[0193] The tensile modulus (MPa) was measured according to the method of JIS K7161. The measurement was performed at 60° C. and 80° C. in the extrusion direction (MD) of molding. It can be said that the higher the tensile modulus, the higher the rigidity.

[0194] 〔Wrinkle〕

[0195] The wrinkles in the TD direction on the CPP film of the laminated film were visually observed, and the number of wrinkles was evaluated.

[0196] The meanings of the symbols in Tables 2 and 3 are as follows.

[0197] (Wrinkles)

[0198] ○: less than 2;

[0199] △: 3 to 9;

[0200] ×: 10 or more.

[0201] [Comparative Examples 2 to 5, Examples 1 to 7]

[0202] A laminated film was produced and evaluated in the same manner as in Comparative Example 1 except that the propylene-based polymer was changed as described in Table 2. The results are shown in Table 2.

[0203] [Table 2]

[0204]

[0205] [Comparative Examples 5-1 to 5-3]

[0206] A laminated film was produced and evaluated in the same manner as in Comparative Example 5 except that the formation conditions of the inorganic oxide layer were changed and the type of inorganic oxide and the thickness of the inorganic oxide layer were changed.

[0207] In addition, the color change of the laminated film was also evaluated. A film without an inorganic oxide layer was prepared and observed together with a film after the inorganic oxide layer was formed to visually evaluate whether there was a difference in color tone. The results are shown in Table 3.

[0208] [Examples 6-1 to 6-3]

[0209] The same operation as in Example 6 was carried out except that the formation conditions of the inorganic oxide layer, the type of inorganic oxide and the thickness of the inorganic oxide layer were changed to produce a laminated film and evaluate it. In addition, the laminated film was evaluated for discoloration. The results are shown in Table 3.

[0210] [Table 3]

[0211] Table 3

[0212]

Claims

1. A laminated film, characterized in that: A non-stretched polypropylene film and an inorganic oxide layer in contact with the non-stretched polypropylene, The unstretched polypropylene film contains a propylene polymer satisfying the following conditions (i) to (iii), (i) a melt flow rate (MFR) in the range of 3 to 25 g / 10 min measured at 230° C. and 2.16 kgf load; (ii) the ratio of the weight average molecular weight Mw to the number average molecular weight Mn measured by GPC is in the range of 6 to 15; (iii) The ratio Mz / Mn of the Z average molecular weight Mz to the number average molecular weight Mn measured by GPC is in the range of 40 to 150.

2. The laminated film according to claim 1, wherein: It has gas barrier properties.

3. The laminated film according to claim 1, wherein: The tensile modulus at 80°C is 800 MPa or more.

4. The laminated film according to claim 1, wherein: The inorganic oxide layer has a thickness of 20 to 150 nm.

5. The laminated film according to claim 1, wherein: A biaxially stretched polypropylene film is further provided on the side opposite to the unstretched polypropylene film, in contact with the inorganic oxide layer via an adhesive layer.

Citation Information

Patent Citations

  • Nonorientated polypropylene film metallized with metal oxide

    JP1997143294A

  • Polypropylene-based resin composition and molding comprising the same

    JP2001302858A

  • Highly rigid polypropylene-based composition and production method

    JP2006045446A

  • Propylene-based polymer composition, non-stretched film, and laminate

    WO2021025142A1

  • Propylene polymer composition, unstretched film, and laminate

    CN114207012A